OLHARES SOBRE O OUTRO Estudo das representações do Islã nos jornais Estado de S. Paulo e Folha de S. Paulo - Gomes, Ingrid (2012)
The premise of the study include the existence of forces of power in the portrayals of Islam in international journalism. It is known that Islam, in cultural and political terms, has increased visibility from the acts of September 11, 2001. In this sense, the research finds that this moment plays in history, a political phenomenon of strong impact and ideological significance. As the object of analysis, the study addresses the discursive representations (Discourse Analysis) and the interconnections with (and) Islam in the Folha de S. Paulo and the Estado de S. Paulo, with the corpus of the material published by the newspapers, the International Editorial Board, within 15 days before and after the date that marked historically, 10 years of the attack on the Twin Towers. The thesis also makes an inventory of historical and cultural formation of the East and Modern Islam, the construction of the story Unlike Islam and the Other, and the rescue of international journalism. There was, in generalizations and simplifications of the media representations of Islam analyzed, an approximate depiction of the actions of Islamic fundamentalists, instructing the complex context of Islam as the Other, the different current history, denying him his cultural attributes of authenticity and otherness.